2011
DOI: 10.1186/1744-859x-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Disability and health-related quality of life in outpatients with generalised anxiety disorder treated in psychiatric clinics: is there still room for improvement?

Abstract: ObjectiveWe assessed the impact of generalised anxiety disorder (GAD) on disability and health-related quality of life in outpatients treated in psychiatric clinics via a secondary analysis conducted in 799 patients from a cross-sectional study of prevalence of GAD in psychiatric clinics.MethodsPatients were allocated into two groups: follow-up (15.7%) and newly diagnosed patients (84.3%), and were administered the Hamilton Anxiety Scale (HAM-A), Clinical Global Impressions Scale (CGI), Sheehan Disability Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…The GAD-SUD group, even after improving from Wave 1 to Wave 2 in mental health-related quality of life, had scores consistently below 50, which was the mean across most scales for the SUD only group. These findings are consistent with other evidence suggesting GAD comorbidity confers increased risk for impairment, poor functioning, and quality of life (Grant et al, 2005), which may be due to the somatic manifestations of GAD and impact on physical discomfort and pain (Bobes et al, 2011), as well as the impact of GAD on numerous areas of one’s life, including work performance (Kessler et al, 1999; Wittchen, 2002) and social functioning (Henning et al, 2007) that often subsists even following treatment for individuals with GAD (Bobes et al, 2011). …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The GAD-SUD group, even after improving from Wave 1 to Wave 2 in mental health-related quality of life, had scores consistently below 50, which was the mean across most scales for the SUD only group. These findings are consistent with other evidence suggesting GAD comorbidity confers increased risk for impairment, poor functioning, and quality of life (Grant et al, 2005), which may be due to the somatic manifestations of GAD and impact on physical discomfort and pain (Bobes et al, 2011), as well as the impact of GAD on numerous areas of one’s life, including work performance (Kessler et al, 1999; Wittchen, 2002) and social functioning (Henning et al, 2007) that often subsists even following treatment for individuals with GAD (Bobes et al, 2011). …”
Section: Discussionsupporting
confidence: 92%
“…This may be due to the impact of GAD on work productivity, employment status, and overall daily functioning (Bobes et al, 2011; Henning et al, 2007), or the overall higher levels of impairment associated with greater comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Despite various treatment options, between 25% and 40% of patients do not respond to treatment in clinical trials , and as many as 32% discontinue study treatment as a result of adverse events (AEs) . Moreover, a recent comparison of newly diagnosed GAD patients and treated patients showed that, despite a significantly lower mean Hamilton Anxiety Scale (HAM‐A) total score (26.8 newly diagnosed vs. 22.4 treated; p < 0.001) in the treated group, scores on patient‐reported functional impairment on the Sheehan Disability Scale (SDS) were not statistically significantly different in the treated vs. newly diagnosed groups . These findings emphasise the need for alternative therapies that can provide efficacy to a larger proportion of patients with GAD and accelerate their functional recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Generalized anxiety disorder (GAD) is a chronic, impairing (Bobes, Caballero, Villardaga, & Rejas, 2011) condition characterized by frequent and persistent worry. Although cognitive behavioral therapy appears efficacious for GAD (Colvin, Ouimet, Seeds, & Dozois, 2008), a quarter (Ladouceur et al, 2000) to three quarters (Waters & Craske, 2005) of patients may not achieve high-end state functioning by treatment completion.…”
mentioning
confidence: 99%